Cooling Characteristic Of Carrot Puree - Purbasari, Dian; Setya Budi, Jaya Bagus; Taruna, Iwan (Protech Biosystems Journal, 2022)
Carrot is a plant that stores carbohydrates in large quantities, post-harvest processing of carrot in Indonesia still limited to get processed into the main ingredients of dishes. This study used two factor, ratio of carrot and water, and lenght of grinding time. The stage of measuring cooling characteristic start with the preparation of raw carrot, washing, peeling, cutting, grinding, and the cooling process (6°C). Cooling characteristic measured are the changing in temperature of puree during cooling process and cooling rate. This study used  the ratio of carrot and water 1:1 (100 gr:100 ml), 1:2 (100 gr:200 ml), 2:1 (200 gr:100 ml), and the lenght of grinding were 1, 2, and 3. The data was taken from 9 samples of treatment combinations. Changed values of combination temperature ranged from 26.98°C to 16.76°C, 27.44°C to 16.79°C, 28.79°C to 17.29°C, 25.81°C to 15.52°C, 28.04°C to 19.03°C, 29.99 to 19.19°C, 26.56°C to 16.96°C, 27.81°C to 19.10, and 27.72 °C to 19.53 °C. Highest average cooling rate occured in the first 5 minutes when the material temperature was still higher than the cooling medium, the cooling rate values in a row were: 0.21; 0.20; 0.30; 0.22; 0.20; 0.20; 0.14; 0.16; and 0.15.